2016
DOI: 10.1002/jbm.b.33712
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of hybrid patches composed of PLA based copolymers and collagen/chondroitin sulfate for ligament tissue regeneration

Abstract: Biomaterials for soft tissues regeneration should exhibit sufficient mechanical strength, demonstrating a mechanical behavior similar to natural tissues and should also promote tissues ingrowth. This study was aimed at developing new hybrid patches for ligament tissue regeneration by synergistic incorporation of a knitted structure of degradable polymer fibers to provide mechanical strength and of a biomimetic matrix to help injured tissues regeneration. PLA- Pluronic (PLA-P) and PLA-Tetronic (PLA-T) new copol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Until now, no such approach has been tested. Pinese et al combined PLA polymers as knitted patches with collagen/chondroitin sulfate for ligament regeneration [ 52 ]. Heo et al combined PLA with gelatin hydrogels and showed that human adipose-derived stem cells can be drifted to osteogenic differentiation and suggest this material for bone tissue engineering [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Until now, no such approach has been tested. Pinese et al combined PLA polymers as knitted patches with collagen/chondroitin sulfate for ligament regeneration [ 52 ]. Heo et al combined PLA with gelatin hydrogels and showed that human adipose-derived stem cells can be drifted to osteogenic differentiation and suggest this material for bone tissue engineering [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Then, a remarkable discrepancy with a sharp decline of M η was observed for the third and sixth month, suggesting the occurrence of rapid decomposition for PLLA1. The reversal of the degrading rate in PLLA1 probably resulted from the increment of the pH value due to the dissolution of more hydrophilic MgO whiskers in relatively long-term degradation, which accelerated the hydrolysis of PLLA since it had a higher decomposing rate in an alkaline environment [37].…”
Section: Resultsmentioning
confidence: 99%
“…In Figures 2A,B, there is an increasing evolution of SI curves with time for all PLA fibers whatever the temperature meaning that the degradation mechanism predominantly occurring in the matrix is chain scission (Gajjar and King, 2014;Gil-Castell et al, 2014). Indeed, the literature (Elsawy et al, 2017) reported that under humid conditions, hydrolysis reactions occur between PLA ester groups and water molecules resulting in chain scission forming chain segments with low molecular weight (Girdthep et al, 2016;Lins et al, 2016;Lorenzo et al, 2016;Mohammad et al, 2016;Pinese et al, 2016;Stloukal et al, 2016;Yang et al, 2016). Moreover, the hydrolysis of PLA bionanocomposites is strongly dependent on the intrinsic characteristics of PLA matrix, the nature of fillers, their dispersion in the polymer and the environment conditions (humidity and temperature) (Zhou and Xanthos, 2008;Maharana et al, 2009).…”
Section: Scission Index Evolutionmentioning
confidence: 92%